Delirium: A Marker of Vulnerability in Older People - Bellelli, Giuseppe; Brathwaite, Justin S.; Mazzola, Paolo (Frontiers in Aging Neuroscience, 2021)
Delirium is the clinical expression of an acute cerebral dysfunction caused by various noxious insults. Its prevalence is very high in the elderly, especially in the hospital setting, and in older patients it can be the presenting symptom of an acute underlying disease. Delirium is associated with several adverse clinical and functional outcomes, along with cognitive decline, institutionalization, and short- and long-term mortality. It is thus crucial to increase the attention on this geriatric syndrome, which has been demonstrated to be prevented in a large proportion of cases. Delirium is not only a marker of patient vulnerability and clinical instability, but also an index of the quality of care and the efficiency of its organization. By systematically assessing the presence of delirium during the whole length of hospital stay, physicians may closely monitor the patient’s clinical status. The aims of this chapter are to review the current clinical practice in delirium, focusing particularly on older and frail individuals. The topics covered include epidemiology and outcomes, causes, clinical features and diagnosis, prevention and treatment. Finally, implications for clinical practice are discussed.